185k views
3 votes
Solve the equation
-10x + 1 + 7x = 37

2 Answers

3 votes

Answer:


x = -12

Explanation:

Step 1: Combine like terms


(-10x + 7x) + 1 = 37


-3x + 1 = 37

Step 2: Subtract 1 from both sides


-3x + 1 - 1 = 37 - 1


-3x = 36

Step 3: Divide both sides by -3


-3x / -3 = 36 / -3


x = -12

Answer:
x = -12

User Phoneswapshop
by
4.9k points
4 votes

Answer:

x = -12

Explanation:

-10x + 1 + 7x = 37

Combine like terms

-3x +1 = 37

Subtract 1 from each side

-3x +1 -1= 37-1

-3x = 36

Divide each side by -3

-3x/-3 = 36/-3

x = -12

User Ashish Babu
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.